Counseling on the Selection of Contraceptive Devices for Women of Childbearing Age at Banjar Basa, Marga Village Tabanan - Diyu, Ida Ayu Ningrat Pangruating; Mastryagung, Gusti Ayu Dwina (Jurnal Abdimas ITEKES, 2021)
Indonesia as a developing country with a large population is greatly helped by the contraception method to reduce population and improve women's health. The types of saline contraception start from MKJP and Non-MKJP. Each type of contraception has advantages and disadvantages and each has an individual suitability and suitability for each woman. Providing complete information is an important factor in choosing a contraceptive device. The provision of information related to contraceptives and their types as well as health detection in women after childbearing is optimized to increase the coverage of active family planning participants and reduce high-risk groups who are not allowed to use certain contraceptive methods. From the activities carried out, it was obtained from 15 women of childbearing age who participated in this activity as many as 6 people (40%) had good knowledge regarding contraception and as many as 9 people (60%) had less knowledge about contraception. After being given education, there was a significant increase in the understanding of women of childbearing age regarding contraception, namely as many as 15 people (100%).